Genomic diversification of IncR plasmids from China. (December 2019) - Jing, Ying; Jiang, Xiaoyuan; Yin, Zhe; Hu, Lingfei; Zhang, Ying; Yang, Wenhui; Yang, Huiying; Gao, Bo; Zhao, Yuee; Zhou, Dongsheng; Wang, Chengbin; Luo, Yanping
Highlights: Eight IncR plasmids from China possessed conserved IncR backbones composed of repB, parAB, umuCD, retA and resD . Complex homologous recombination events occurred during resistance accessory module evolution, making them differ markedly. Accessory modules carried distinct resistance markers, promoting accumulation and spread of antimicrobial resistance. One or more regions responsible for plasmid replication/maintenance were found in some resistance accessory modules. These regions facilitate stable replication of corresponding IncR plasmids at steady-state copy numbers. Abstract: Objectives: The aim of this study was to perform a detailed genomic characterisation of IncR plasmids from China. Methods: Three IncR plasmids (p13190-tetA, p02085-tetA and p30860-tetA) from clinical isolates of Klebsiella pneumoniae, Citrobacter freundii and Enterobacter cloacae, respectively, were fully sequenced using high-throughput genome sequencing and were compared with five previously sequenced IncR plasmids (pHN84KPC, pSH-01, pK245, pKPC_P16 and pKPC-LK30) from China. Results: The eight IncR plasmids from China possessed conserved IncR backbones composed of repB, parAB, umuCD, retA and resD. Resistance accessory modules integrated into the IncR backbones included multidrug resistance (MDR) regions in p30860-tetA, p02085-tetA, p13190-tetA and pK245, bla KPC-2 regions in pHN84KPC, pKPC-LK30 and pKPC_P16, and the ΔTn 1721 – sil region in pSH-01. These resistance accessory modules were inserted at a site between retA and vagD, resulting in loss of the backbone genes vagCD in some of the plasmids. The resistance accessory modules differed dramatically from one another and carried distinct profiles of resistance markers. In particular, all of p13190-tetA, p02085-tetA, p30860-tetA, pHN84KPC, pSH-01 and pK245 carried tetracycline resistance tet gene modules, and the carbapenemase gene bla KPC-2 was identified in pHN84KPC, pKPC-LK30 and pKPC_P16. In addition, one or more regions responsible for plasmid replication and/or maintenance were found in some of the resistance accessory modules, facilitating stable replication of corresponding IncR plasmids at steady-state copy numbers. Conclusions: This detailed comparative genomics analysis of IncR plasmids from China provides a deeper insight into the diversification and evolution of IncR plasmids.